Teacher’s Difficulties in Teaching Oral Communication Skills in Indonesia: A Comparative Literature Review - Utami, Valisneria (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
While oral communication skills is considered as an indicator of foreign language proficiency, in Indonesia, these skills seems to receive minium attention. As a result, the learning outcomes, still far from satisying. According to the literatures, teacher’s still encountered difficulties in teaching speaking and listening and hesitance to utilized English language in the classroom. This present study aimed to present comparative literature review of research studies related to teacher’s difficulties in teaching oral communication skills. First the study explains about communicative competence and listening model. Second, this study demonstrates the condition of oral communciation teaching in Indonesia and its relationship to the teachers’ competence. Thirdly, this study explore other Asian contexts. These contexts are compared and contrasted, thus some similarities and differences are highlighted. Finally, some practical implications and suggestions for further researches are offered.